Management Resource Values - A. B. Bakuradze (Образование и наука)
The paper looks at the managerial resource values guaranteeing the effective functioning and development of any social institution. The main emphasis is on the asset management in educational sphere and optimizationopportunities of organizational processes. The human, logistical, technical, informational and time resources ofmanagerial activity are outlined and specified from the strategic perspective and effectiveness standpoint. The necessary criteria of a strategic resource are identified as the value, rarity, originality and indispensability. The author makes a conclusion about the priority of human resources in the value hierarchy of social organization in the era of information society. The paper demonstrates both the theoretical and practical ways and means of raising the effectiveness and efficiency of educational institutions, as well as the constant need for teacher’s training, retraining, and stimulation of self-education. The investment in human resources and motivating environment, aimed at developing the potential of academic staff and other employees of educational institutions, benefits both the managers and employees alike and leads to social partnership, harmony, and conciliation of economic and social interests within the organization.